2020
DOI: 10.1186/s12957-020-1801-7
|View full text |Cite
|
Sign up to set email alerts
|

Anal function and quality of life analysis after laparoscopic modified Parks for ultra-low rectal cancer patients

Abstract: Background: To assess postoperative anal function and quality of life of ultra-low rectal cancer patients treated by laparoscopic modified Parks surgery. Methods: From February 2017 to March 2019, 114 patients with ultra-low rectal cancer above T2 were treated respectively with ultra-low anterior resection (Dixon), modified coloanal anastomosis (modified Parks), and Miles according to the preoperative stage and anastomotic position. The postoperative anal function and Fecal Incontinence Quality of Life Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…Many previous studies have proved that obesity is an important risk factor for prolonged operation time [23]. Especially for ultra-low rectal cancer, obesity and narrow pelvis will increase the di culty of free and anastomosis, thus increasing the operation time [24]. However, this study found that BMI was not an independent risk factor affecting the operation time of CSPO.…”
Section: Discussioncontrasting
confidence: 57%
“…Many previous studies have proved that obesity is an important risk factor for prolonged operation time [23]. Especially for ultra-low rectal cancer, obesity and narrow pelvis will increase the di culty of free and anastomosis, thus increasing the operation time [24]. However, this study found that BMI was not an independent risk factor affecting the operation time of CSPO.…”
Section: Discussioncontrasting
confidence: 57%
“…Mainly, laparoscopic tumor-specific mesorectal excision (TSME) has been utilized for upper rectal cancer [ 22 ]. Many problems that cannot be solved by conventional laparotomy, such as anus-preserving surgery for rectal cancer with anal distance less than 5cm, can be solved by laparoscopic technique, which significantly improves the life quality of patients [ 23 , 24 ]. Laparoscopic surgery has many advantages, such as a clear vision of operation, small incision, mild postoperative pain, and short hospital stay [ 25 – 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient follow-up varied from 6 months to 5 years. Only four 30 , 34 , 35 , 37 of the included studies provided preoperative QoL data and then followed patients up; two other papers 26 , 41 provided serial QoL measurements, but not preoperative data. Thirteen studies provided only one measure of postoperative QoL, with no preoperative data.…”
Section: Resultsmentioning
confidence: 99%